Determination of Sulphur Content in Fuel while Using Inversion Voltammetric Method - N. P. Matveyko; A. M. Braykova; A. S. Kalinichenko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper describes the developed methodology for sulphur determination with the help of  an inversion voltammetry. The method includes an electrode regeneration at 500 mV (in reference to silver chloride electrode) within 20 sec, sulphur concentration at 100 mV, registration of cathode current-potential curve with 200 mV/sec and within potential interval from 100 up to 400 mV.